Trends in the Development of the Digital Economy in Republic of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
This article examines the relevance of articles related to the development and popularization of information and communication technologies, as well as the digital world in all areas of our life from the moment we spend our time to our money management skills. In addition, the article provides information on the basic principles of the digital economy, increasing efficiency and creating “digital enterprises”. And also, information and other high technologies have become an integral part of everyday life, almost the entire world population. ICT penetrates and influences even the most remote and underdeveloped regions of the planet, becoming a key factor in the development, innovation and prosperity of economies. Security issues in IT have become the object of attention of many companies specializing in information security.